Koboltatal , Republik Moldau: Studien zu den Kulturbeziehungen der Sântana-de-Mureş-Kultur zwischen Pruth und Dnjestr - Voß, Hans-Ulrich (e-Forschungsberichte des DAI, 2023)
Together with the Department of Historical Research of the „Ion Creangă“ State Pedagogical University of Chişinău (Moldova) and the National Museum of the Eastern Carpathians in Sfântu Gheorghe (Romania) the investigation of a late Roman/early Migration period settlement of the Sântana-de-Mureş- Culture (c. 230–430/450 AD) on the southern slope of the Kubolta Valley at Putinești, Raionul Florești, has been continued with geomagnetic prospection and aerial photogrammetry. The settlement was already known from field walking. The site is part of an area of settlement some 9,0 km long on the eastern edge of the Kubolta-valley, an area intensively colonised already in prehistoric times (Neolithic, Bronze Age).